Public Relations Activities in Building Positive Relations with Apartment Residents: A Descriptive Study at Sunter Parkview Apartments (Oratio Directa, 2023)
Public relations contributes to organizational harmony and to constructive relations among residents of an apartment community. This qualitative descriptive study examines public relations activities at Sunter Parkview Apartments through field interpretation, interviews, and organizational observations. Excellence theory in public relations and participation theory provide the analytical framework. The findings show that resident socialization, blood-donation activities, routine communication, and complaint handling support two-way communication between management and residents. These activities help circulate operational information, accommodate resident aspirations, and strengthen community relations, although complaint resolution remains constrained by operational procedures and response time.
Keywords: Public relations; Apartment residents; Excellence theory; Organizational communication; Community relations